ПОМОГИТЕ,плиз [latex] \sqrt{5+x^2} + \sqrt{5-x^2} =4 [/latex] [latex] \sqrt{x-4 \sqrt{x+4} } =3[/latex]

ПОМОГИТЕ,плиз [latex] \sqrt{5+x^2} + \sqrt{5-x^2} =4 [/latex] [latex] \sqrt{x-4 \sqrt{x+4} } =3[/latex]
Гость
Ответ(ы) на вопрос:
Гость
Решение 1)  √(5 + x²) + √(5 - x²) = 4 ОДЗ: 5 + x² ≥ 0, 5 - x² ≥ 0,  [√(5 + x²)]²  = [4 - √(5 - x²)]² 5 + x² = 16 - 8*√(5 - x²) + 5 - x² 2x² - 16 = - 8*√(5 - x²) 16 - 2x² = 8*√(5 - x²)  делим обе части уравнения на 2 8 - x² = 4*√(5 - x²) [8 - x²]²  = [4*√(5 - x²)]² 64 - 16x² + x⁴ = 4*(5 - x²) 64 - 16x² + x⁴ = 20 - 4x² x⁴  -12x² + 44 = 0 x⁴ - 15x² + 44 = 0 x² = y y² - 15y + 44 = 0 D = 225 - 4*1*44 = 225 - 176 = 49 y₁ = (15 - 7)/2 y₁ = 4 y₂ = (15 + 7)/2 y₂ = 11 x² = 4 x₁ = - √4 = 2 x₂ = √4 = 2 x² = 11 x₃ = - √11 x₄ = √11 Проверка: х = - 4 √(5 + (-2)²) + √(5 - (-2)²) = 3 + 1 = 4 4 = 4 Верно x = 4 √(5 + 2²) + √(5 - 2²) = 3 + 1 = 4 4 = 4 Верно x = - √11 √(5 + (-√11)²) + √(5 - (-√11)²) =4 + √(-6) не имеет смысла x =  √11 √(5 + (√11)²) + √(5 - (√11)²) =4 + √(-6) не имеет смысла Ответ: x = - 2; x = 2 2) √[x - 4√(x + 4)] = 3 ОДЗ:  [√(x - 4√(x + 4)]² = 3² x - 4√(x + 4) = 9 4√(x + 4) = x - 9 [4√(x + 4)]² = (x - 9)² 16*(x + 4) = x² - 18x + 81 x² - 18x + 81 - 16x - 64 = 0 x² - 34x + 17 = 0 D = 1156 - 4*1*17 = 1088 x₁ = (34 - 8√17)/2 x₁ = 17 - 4√17 x₂ =  (34 +  8√17)/2 x₂ = 17 +  4√17
Не нашли ответ?
Ответить на вопрос
Похожие вопросы